Relevance of location in the University-Business relationship: analysis of the origin of Spanish universities graduates employed in IBEX35 companies - Moreno-Delgado, Alicia; Orduña Malea, Enrique; Repiso, Rafael (Revista General de Información y Documentación, 2020)
The objective of this work is to deepen the university-company relationship by studying the way in which IBEX35 companies hire graduates from Spanish universities. In this regard, this paper analyses how the location of both companies and universities affects the hiring of graduates. To this end, data has been collected on the number of university graduates working for each of the IBEX35 companies using the information contained on LinkedIn. The statistical analysis has identified how universities are clustered in relation to the number of graduates they provide to those companies. Our results indicate that the companies attract graduates mainly from universities located in the same geographical area as their headquarters. In addition, universities located at some distance from large economic and industrial centers provide these companies with fewer employees.